Level Of Financial Literacy And Its Influencing Factors Among Dairy Farmers In Pangalengan District Bandung - Sisva, Yuuki Zharfan; Rachmina, Dwi; Feryanto, Feryanto (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
Research on the level of financial literacy of farmers is needed to measure their ability to manage finances to improve their level of welfare. This study aims to analyse the level of financial literacy of dairy farmers and the factors that influence it and see its relationship with farmers' preferences in facing risks. This research was conducted in Pangalengan District, Bandung Regency using descriptive analysis method, multiple regression analysis, and Pearson correlation test. The number of respondents in this study was 77 farmers spread across three villages in Pangalengan District, Bandung Regency. The results showed that the financial literacy level of the majority of farmers (77%) was in the less literate category, especially in the financial behaviour component. Factors that can affect the financial literacy of farmers are income, age, education level, ownership of other jobs, and distance to financial institutions. While the variables of length of farming and gender do not influence the level of financial literacy of farmers and prove a positive relationship between the level of financial literacy with their preferences in facing risks.